An Investigation of the Impact of Research-led Education on Student Learning and Understandings of Research. - Jiang, Fuming; Roberts, Pamela (Journal of University Teaching and Learning Practice, 2011)
This study investigated the impact of two approaches to research-led education on students’ learning and their understandings of research in the context of two university courses in international business involving third year undergraduate and graduate students. One approach involved the lecturer using his research as the basis for a case-study assignment involving an intercultural business negotiation. In the second approach students conducted a research project in which they reviewed the academic literature to identify practical implications for business and theoretical gaps as the basis for future research. A questionnaire was used to explore students’ perceptions of the impacts on their learning and understandings of research. Students’ understandings of research were most informed by the research based learning project which was presented to them as an experience of doing research. Students valued the lecturer using his research in the course because of his enthusiasm and his expertise and mentoring in doing research. However many students developed only limited understandings of research in the subject area, despite their direct experience of the lecturers’ research. The implications for the design of research-led education approaches are explored.